1996
DOI: 10.1111/j.1744-6155.1996.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Among Black Mothers: Evidence Supporting the Need for Prenatal Intervention

Abstract: PURPOSE. To identify factors that might be targeted for intervention to increase breastfeeding among black mothers DESIGN. Secondary analysis of the 2988 National Maternal Infant Health Survey PARTICIPANTS. Black mothers (N = 5,142) from a nationally representative sample of mothers who had births in 2988 MAIN OUTCOME MEASURES. Breastfeeding rates RESULTS. Factors associated with breastfeeding included a mother's plan to breastfeed; Women, Infants and Children (WIC) advice, or advice from a prenatal-care provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…These findings are consistent with previous observations in the United States that black women were less likely to breastfeed than nonblack women. [19][20][21][22] Consistent with observations in other developed countries, 23,24 we also observed a strong inverse association between how poor a family was and the rate of breastfeeding. Although we did not investigate whether the low breastfeeding rates among black women could be attributed to generally poorer socioeconomic status, the evidence of racial/ethnic disparities in breastfeeding supports the need for research that identifies social, cultural, economic, and psychological factors that can be targeted for interventions to increase breastfeeding rates among black women.…”
Section: Discussionsupporting
confidence: 79%
“…These findings are consistent with previous observations in the United States that black women were less likely to breastfeed than nonblack women. [19][20][21][22] Consistent with observations in other developed countries, 23,24 we also observed a strong inverse association between how poor a family was and the rate of breastfeeding. Although we did not investigate whether the low breastfeeding rates among black women could be attributed to generally poorer socioeconomic status, the evidence of racial/ethnic disparities in breastfeeding supports the need for research that identifies social, cultural, economic, and psychological factors that can be targeted for interventions to increase breastfeeding rates among black women.…”
Section: Discussionsupporting
confidence: 79%
“…Most studies that identify predictors of breastfeeding behavior have been done with samples of predominantly White women of moderate incomes. However, Timbo, Headrick, and Klontz (1996), using a random sample of Black women from 48 states, found that breastfeeding rates in Black women increased with increasing age, education, and income, which is also noted in studies with White women. Chin et al (2008) reported that higher education was associated with higher breastfeeding initiation in both Black and White women, although no interaction was found between race and education in their analysis.…”
Section: Psychosocial Factorsmentioning
confidence: 64%
“…1,2 Despite these recommendations, the overall rate of breast-feeding in the United States in the early postpartum period is only 73.8 ± 1.0%. [4][5][6][7][8] Among Latina * women in the United States, the initiation of breast-feeding is higher than Sociocultural Influences on the Determinants 319 that among white women. It is well documented that African-American women in the United States breast-feed less often than white women.…”
mentioning
confidence: 99%